Acute idiopathic pulmonary hemorrhage in infants. Report of two cases and literature review - Alexandra Bastidas Jacanamijoy; Delia Carolina García Silva; Juan Carlos Barrios Méndez; Juan David Roa; Pablo Vásquez (Case Reports)
Acute idiopathic pulmonary hemorrhage is a rare life-threatening disease in children. The classic triad includes hemoptysis, anemia and respiratory distress. Since clinical presentation may vary, diagnosis can be difficult. Severe respiratory distress, and ventilatory failure requiring mechanical ventilation are often present. Chest X-rays usually show unilateral or bilateral infiltrates, therefore, other causes of pulmonary hemorrhage must be excluded, since most of them correspond to systemic diseases. Treatment often requires intravenous steroids to solve the respiratory failure in most cases.